2023
DOI: 10.1007/s12672-023-00690-7
|View full text |Cite
|
Sign up to set email alerts
|

ABHD17C, a metabolic and immune-related gene signature, predicts prognosis and anti-PD1 therapy response in pancreatic cancer

Abstract: Background PDAC is a highly malignant and immune-suppressive tumor, posing great challenges to therapy. Methods In this study, we utilized multi-center RNA sequencing and non-negative matrix factorization clustering (NMF) to identify a group of metabolism-related genes that could effectively predict the immune status and survival (both disease-free survival and overall survival) of pancreatic ductal adenocarcinoma (PDAC) patients. Subsequently, thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Moreover, although the series of SNPs did not reach a significantly associated threshold, they still had high-correlation signals distributed throughout the intergenic region between ARNT2 and ABHD17C and the HOMER2 gene in CHR18. However, studies related to ARNT2 and ABHD17C have focused on the fields of cancer and immunity [41,42]. Other researchers have shown that HOMER2 is expressed in osteoblasts [43,44].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, although the series of SNPs did not reach a significantly associated threshold, they still had high-correlation signals distributed throughout the intergenic region between ARNT2 and ABHD17C and the HOMER2 gene in CHR18. However, studies related to ARNT2 and ABHD17C have focused on the fields of cancer and immunity [41,42]. Other researchers have shown that HOMER2 is expressed in osteoblasts [43,44].…”
Section: Resultsmentioning
confidence: 99%